Prognostic Value of Neutrophil-to-Lymphocyte Ratio in Cats With Hypertrophic Cardiomyopathy - Fries, Ryan C.; Kadotani, Saki; Stack, Jonathan P.; Kruckman, Leah; Wallace, Gabrielle (Frontiers in Veterinary Science, 2022)
Objective To assess the prognostic value of neutrophil-to-lymphocyte ratio (NLR) for cardiac death in cats with hypertrophic cardiomyopathy. Study Design Prospective observation study Animals Ninety-six client-owned cats Methods Complete blood count samples were collected from 38 healthy and 58 hypertrophic cardiomyopathy (HCM) cats and NLR ratios were analyzed. All cats had echocardiographic measurements performed on the same day as blood collection. Spearman rank correlation was used to assess the relationship between echocardiographic measurements and NLR. Long-term outcome data were obtained, and time to cardiac death and variables associated with cardiac death were analyzed using Kaplan-Meier survival curves and Cox proportional hazards models respectively. Results The NLR was significantly higher in cats with confirmed congestive heart failure. When evaluating HCM patients, cats in the third NLR tertile had a significantly higher risk of cardiac death with a hazard ratio of 10.26 (95% CI: 1.84 – 57.14; p = 0.0001) when compared with that of patients in the first tertile. NLR was significantly associated with echocardiographic measures of left atrial size, left auricular function, and the presence of left atrial spontaneous echo contrast (SEC) and thrombus formation. Conclusions and clinical relevance Increased neutrophil-to-lymphocyte ratio is a negative prognostic indicator in cats with hypertrophic cardiomyopathy.